Las necesidades formativas docentes de los profesores universitarios - Estepa Murillo, Paulino; Mayor Ruiz, Cristina; Hernández, Elena; Sánchez, Marita; Rodríguez, José María; Altopiedi, Mariana; Torres, Juan Jesús (Revista Fuentes, 2005)
En este artículo pretendemos analizar las necesidades formativas docentes de los profesores noveles universitarios y de los profesores en general de las Universidades de Sevilla y Huelva. No resulta extraño decir que la titulación universitaria se ocupa fundamentalmente de preparar a los alumnos para desempeñar tareas en el mundo profesional de la empresa más que para desempeñar tareas en la institución universitaria. Debido a ello, los profesionales que deciden continuar en la vida universitaria encuentran verdaderos problemas a la hora de comenzar su actividad profesional como docentes, detectándose, por tanto, determinadas necesidades formativas en lo que se refiere fundamentalmente a la utilización de estrategias docentes que mejorarían su incorporación al mundo de la docencia universitaria. Estos profesores reclaman formación y asesoramiento pedagógico y didáctico para la mejora de su tarea docente, es decir, propuestas formativas adecuadas al desempeño de su papel como profesionales de la educación superior. In this article we try to analyze educational formative necessities and of the professors’ beginner university students advice and of the professors in general at the Universities of Seville and Huelva. The university titulación is in charge of fundamentally of preparing the students to carry out tasks in the professional world of the company more than to carry out tasks in the university institution. Professionals that decide to continue in the university life find true problems when beginning their professional activity as educational, being detected, therefore, certain formative necessities in what refers base to the use of educational strategies that you/they would improve their incorporation to the world of the university docencia. These professors claim formation and pedagogic and didactic advice for the improvement of their educational task, that is to say, appropriate formative proposals to the acting of their paper like professionals of the superior education. The society of the knowledge and of the information in the one that we meet demand every time with more peak the formation of the different professionals that you/they carry out different tasks in the society. A deep concern exists for the formation, what bears, in general, every time a bigger number of formation programs depending on the formative necessities that the professionals present, as well as different forms of consenting to them, mainly the denominated programs and-learning and on-line. In this article the results and conclusions of the necessities of the beginner professors’ of University educational formation are exposed. It is necessary to highlight that the publications that have taken place in the last times point out that the university professors, the same as other professionals, require for their improvement as other partners’ educational supports and other colleagues’ specific advice with more experience professional, as well as certain didactic formation. In this sense, the formation programs for professors contribute to the improvement of the educational quality, and therefore, educational, of the university institutions, helping this way to the professors to carry out, the same as in other professions, their list like educational.